Peningkatan Penjualan melalui Brand Loyalty - Fenny Chaindra Tanuwijaya; Nuno Sutrisno (Media Bisnis, 2022)
This research aims to determine the effect of Brand Evaluation, Trust, Satisfaction, Brand Relationship, Brand Affect, Brand Image, and Product Quality on Brand Loyalty users of Dettol antiseptic bath soap in DKI Jakarta. The population in this study was the customers of of Dettol antiseptic bath soap, living in DKI Jakarta. The samples were 146 respondents by purposive sampling method. The Assessment of each variable used 5 points of Likert Scale. Data processing used multiple regression. The results of this study indicate that there is an influence Trust, Satisfaction, Brand Image, and Product Quality on Brand Loyalty of Dettol antiseptic bath soap in DKI Jakarta.